Using a Stakeholder Analysis to Improve Systems Modelling of Health Issues: The Impact of Progesterone Therapy on Infant Mortality in Ohio. (9th November 2018) - Hosseinichimeh, Niyousha; Kim, Hyunjung; Ebrahimvandi, Alireza; Iams, Jay; Andersen, David
Abstract : Systems modelling of health issues enriches analysis of health care policies by exploring interdependencies among system components. Considering a wide range of stakeholder behavior is a requisite for developing a useful model. Our paper shows how to systematically identify stakeholder behavior, formulate them in a model and test their impact on health outcomes. Stakeholder behavior are explained in the context of a simulation‐based analysis of infant mortality in Ohio. Using group model building techniques, we identify three levels of stakeholder behavior—individual, organizational and policy behaviors—and discuss how these behaviors are reflected in the model formulation and drive the key health outcomes. Specifically, we show how individual and policy behaviors are formulated to examine their influence on the impact of progesterone therapy—one of the interventions identified in the group model building session—on infant mortality. We conclude with recommendations for incorporating diverse stakeholder perspectives in systems modelling of health issues. © 2018 John Wiley & Sons, Ltd.